Determinasi Sikap Guru terhadap Profesinya, Konsep Diri, dan Iklim Kerja Sekolah terhadap Kinerja Guru Sekolah Dasar - Sugiarta, Made Pasek; Dantes, Nyoman; Natajaya, Nyoman (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2017)
This study aims to determine the attitude of teachers towards professionalÂ  determination, self-concept, and the climate of primary school to the performance. This study is â€œex-post factoâ€ population of 83people, 73 people sample. Data collection tool is in the form of questionnaires, data analysis with regression techniques. TheÂ  result showed that: (1) there is a significant determinant between teacher attitudes the profession with teacher performance with the correlation coefficient of 0.401, (2) there is a significant determinant between self-concept of teachers with teacher performance with the correlation coefficient of 0.325, (3) there is a determination significant difference between the climate of the school with teacher performance with correlation coefficient of 0.337, contributing 11.3% and the effective contribution of 6.2%, (4) the co-operation between teachersâ€™ attitudes towards the profession, self-concept, and work climate with performance teachers with multiple correlation coefficient of 0.465 and a 21.6% contribution to the performance of teachers.